The Roll of Toll-Like Receptor 4 in the Pathogenesis of Spinal Cord Injury. (16th November 2020) - Banerjee, Christopher; Fessler, David; Vender, John R; Dhandapani, Krishnan
Abstract: INTRODUCTION: Despite decades of research, clinically efficacious treatment options for spinal cord injury (SCI) are lacking. This dearth of therapeutic agents is due, at least in part, to the complex and poorly defined mechanisms underlying delayed, secondary injury after SCI. In the present study, we hypothesized that toll-like receptor 4 (TLR4) promotes secondary injury after SCI. METHODS: SCI was induced using a pre-clinical forceps compression model of SCI in mice. Functional motor recovery was assessed in wild-type (C3H/OuJ) and TLR4 mutant (C3H/HeJ) mice using the Basso Mouse Scale (BMS) and the modified Tarlov scale (mTarlov). TLR4 protein expression and cellular localization were assessed by Western blotting and by immunohistochemistry, respectively. Neurodegeneration was visualized by fluoro-jade B, a sensitive measure of dead/dying cells. RESULTS: TLR4 was biphasically upregulated after SCI, with an acute induction lasting less than 12 hours followed by a delayed increase in expression beginning at 2 days post-SCI. TLR4 expression was restricted to neurons throughout the study, with no co-localization observed in glial cells. C3H/HeJ (TLR4 mutant mice) exhibited improved motor function on both the BMS and mTarlov scales, as compared to C3H/OuJ mice. The improved in outcomes in C3H/HeJ mice was directly correlated with a reduction in neuronal injury, as assessed by fluoro-jade B staining. CONCLUSION: TLR4 is an important mediator of secondary neurodegeneration and functional loss after compression SCI. These data warrant further exploration of TLR4 as a potential therapeutic target for spinal cord injuries.